The degradation of highly stable oilfield pollutants by supported zero-valent transition metals in a dual-oxidation system - BAI Bingbing; YANG Chenye; DOU Longlong; ZHOU Rui; ZHANG Jie; TANG Ying (Gongye shui chuli)
The peroxydisulfate single-oxidation technology can effectively degrade organic pollutants under the activation of transition metals. However, there are issues such as excessive oxidant dosage, narrow pH range, and secondary pollution caused by metal ions leaching. To address these problems, a highly dispersed supported zero-valent copper catalyst(Cu0@LDHs) was obtained by loading transition metal copper onto hydrotalcite(LDHs) carriers by the impregnation-reduction method. Cu0@LDHs was used to activate the hydrogen peroxide-sodium persulfate(H2O2-Na2S2O8) dual-oxidation system for the degradation of oilfield hydroxypropyl guar gum (HPG). Based on the optimization of reaction conditions, it was found that within the pH range of 3 to 11, the H2O2-Na2S2O8 dual-oxidation system still maintained a high degradation effect on HPG, with degradation rates higher than 76.30% at 25 min, and COD removal rate of 93.91% after 120 min. Cu0@LDHs maintained good catalytic activity even after 5 cycles of regeneration, with HPG degradation efficiency of above 80%. During this process, ·OH and SO4·- were identified as the main active species, and there was a synergistic effect between them. XRD, SEM, and BET characterization of Cu0@LDHs before and after the reaction indicated that the high activity of the catalyst was mainly attributed to the highly dispersed Cu0 on the surface of the hydrotalcite carrier, which exhibited excellent activity and stability.